Comprehensive characterization of chitosan/PEO/levan ternary blend films - TOKSOY ÖNER, EBRU; EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE; KESKİN, SIDDIK SİNAN (ELSEVIER SCI LTD, 2014)
Ternary blend films of chitosan, PEO (300,000) and levan were prepared by solution casting method and their phase behavior, miscibility, thermal and mechanical properties as well as their surface energy and morphology were characterized by different techniques. FT-IR analyses of blend films indicated intermolecular hydrogen bonding between blend components. Thermal and XRD analysis showed that chitosan and levan suppressed the crystallinity of PEO up to nearly 25% of PEO content in the blend, which resulted in more amorphous film structures at higher PEO/(chitosan + levan) ratios. At more than 30% of PEO concentration, contact angle (CA) measurements showed a surface enrichment of PEO whereas at lower PEO concentrations, chitosan and levan were enriched on the surfaces leading to more amorphous and homogenous surfaces. This result was further confirmed by atomic force microscopy (AFM) images. Cell proliferation and viability assay established the high biocompatibility of the blend films. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Exopolysacharide; Levan; Chitosan; Poly(ethylene oxide); Blend film; POLY(ETHYLENE OXIDE); SOLID-STATE; CHITOSAN; TEMPERATURE; MICROSCOPY; MELT